PERSEPSI INTERNAL SUPPORT DAN BUILDING COMMUNITY KEPEMIMPINAN MELAYANI GURU PENDIDIKAN AGAMA KRISTEN - Octavianus, Philia Chr; Kleden, Yakobus Beda; Baun, Soleman; Soinbala, Nuriswan Soinbala (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study was conducted to assess the ability of Christian religious education teachers to establish a school culture that is conducive to growth and service, as well as community development both inside and outside the school. The study aims to measure students' perceptions of internal support and community building by Christian religious education teachers at SMAK Hoineno, North Mollo District, South Central Timor Regency. The method used is quantitative analysis focusing on the validity and reliability of measurement instruments through rating scales. The results show that students feel that Christian religious education teachers often provide support in developing their potential, building a school culture, and delivering good service, including motivation and assistance in helping students achieve success. However, students also assess that there are some areas needing improvement, such as listening carefully and upholding ethical principles. The average student perception of internal support falls into the often occurring category (70.05%), while community building inside and outside the school is rated at 68.4%. This study emphasizes the importance of teachers as servant leaders in creating a positive learning environment and building an inclusive community.